Traceability in stem cell research: from participant sample to induced pluripotent stem cell and back. (January 2016) - Morrison, Michael; Moraia, Linda Briceño; Steele, Jane C
This paper describes a traceability system developed for the Stem cells for Biological Assays of Novel drugs and prediCtive toxiCology consortium. The system combines records and labels that to biological material across geographical locations and scientific processes from sample donation to induced pluripotent stem cell line. The labeling system uses a unique identification number to link every aliquot of sample at every stage of the reprogramming pathway back to the original donor. Only staff at the clinical recruitment site can reconnect the unique identification number to the identifying details of a specific donor. This ensures the system meets ethical and legal requirements for protecting privacy while allowing full traceability of biological material. The system can be adapted to other projects and for use with different primary sample types.